Export import relations dynamics between Ukraine and EU - Kniaz, Sviatoslav; Kizun, Anastasiia (Видавництво Львівської політехніки, 2017)
Ukraine's commodity relations with the EU are considered. The analysis of dynamics of export-import operations on the basis of statistical data is carried out. The main directions of cooperation in the field of foreign trade relations are determined, which is one of the main factors of high level of economic development of the country. On the basis of quantitative indicators, positive and negative structural changes in foreign trade with the EU have been identified for Ukraine.
Keywords: export; import; European Union; Ukraine; commodity relations